2021
DOI: 10.1139/cjz-2020-0101
|View full text |Cite
|
Sign up to set email alerts
|

Body shape and fin size in juvenile Atlantic salmon (Salmo salar): effects of temperature during embryogenesis

Abstract: Temperature during egg incubation and early development influences later life stages of fishes, potentially influencing survival. Throughout its distribution, Atlantic salmon (Salmo salar Linnaeus, 1758) have experienced population declines, and in view of ongoing global warming, we tested if temperature during the earliest developmental stages modified body shape and fin size when temperatures averaged 2.6 vs. 5.6 °C. This temperature difference simulates increases predicted in climate change scenarios. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…But this may not only result from differences in growth. Greenberg et al (2021) observed that 1-year-old juveniles of S. salar incubated as eggs in heated water had a slimmer, more smolt-like body shape than similar-sized S. salar offspring that were produced from colder eggs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…But this may not only result from differences in growth. Greenberg et al (2021) observed that 1-year-old juveniles of S. salar incubated as eggs in heated water had a slimmer, more smolt-like body shape than similar-sized S. salar offspring that were produced from colder eggs.…”
Section: Discussionmentioning
confidence: 98%
“…Greenberg et al . (2021) observed that 1‐year‐old juveniles of S. salar incubated as eggs in heated water had a slimmer, more smolt‐like body shape than similar‐sized S. salar offspring that were produced from colder eggs. This may suggest that the warm offspring were ready for migration younger and smaller than those incubated in colder water.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) reported that the populations of R. temporaria from temporary pools had a higher degree of developmental plasticity than tadpoles of the same species from permanent pools. In contrast, juvenile S. salar incubated as eggs in warm water (7°C) were slimmer than conspecifics incubated in cold water (3°C) (Greenberg et al ., 2021), showing another difference between S. trutta and S. salar .…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, Greenberg et al have found that the temperature at the early life stages of Atlantic salmon could influence its shape afterwards. 369 Thus, factors like FM content and water temperature could be used to shape the appearance of fish and to neutralize the impact caused by changes in FO content and FA profile. Moreover, the effect sizes of many parameters changed more when the duration of experiments was longer for Atlantic salmon, whereas for other species such as European seabass and Gilthead seabream, long-term experiments allowed them to adapt to plant oils and eliminated the variation in effect sizes.…”
Section: Discussionmentioning
confidence: 99%